Multicentric Lymphoma in Fila Brasileiro Puppy: A Case Report - Laoharatchatathanin, Titaree; Klomsatid, Nucharee; Thermtong, Puttipong (Journal of Mahanakorn Veterinary Medicine, 2019)
A 3-month-old male Fila Brasileiro breed, presented with an enlargement of the popliteal lymph node for 1 week. Overall results from the general physical examination were normal except an enlargement of the submandibular, prescapular and inguinal lymph nodes. A biopsy of the popliteal lymph node was performed and lymphoma was diagnosed. A thoracic radiograph did not find evidence of lung metastasis; however the abdominal ultrasound found an enlargement of abdominal lymph nodes (hepatic lymph node, splenic lymph node, jejunum lymph node and medial iliac lymph node). Splenomegaly and diffuse multiple hypo echoic foci in splenic parenchyma were also found from the abdominal ultrasonography. Multicentric lymphoma was diagnosed. The dog was prescribed with a chemotherapy (CHOP protocol), which included the combination of 4 chemotherapeutic agents (cyclophosphamide, doxorubicin, vincristine and prednisolone) for a 25 week treatment duration. The results after chemotherapy showed the lymph nodes decreased in size and an abdominal ultrasound showed the improvement of the lesion in splenic parenchyma when compared to pre chemotherapy. In addition, cytology’s result from fine needle aspiration of popliteal lymph node was also negative from cancer cells after treatment.